(untitled) (Journal of Engineering, 2008)
The paper presented a new type of double helical-winding tubular induction motor (DHWTIM). The proposed motor consists of double- layer helical windings primary arranged on the same circumference with a common secondary. By controlling the phase sequence of supply voltage for each of primary winding layers, the secondary conductor would be capable of producing pure rotary motion, pure linear motion, or helical motion. An appropriate multi-layer analysis using cylindrical geometry is presented. This has been used to study the effect of iron presence in the magnetic circuit of the machine on its performance.